Power relations and the paradox of community participation among the San in Khwee and Sehunong - Molosi, K.; Dipholo, K.; San community (My University, 2016)
The discourse of community participation has been popularised by both Government and Non-Governmental Organisations as a ‘technical fix’ to most community development problems. As such, participation is seen as a necessary condition for empowering grassroots communities such as the San in Botswana. However, despite this claims of empowerment, most often than not, the empowerment fostered under the rubrics of participatory development seems to be perpetuating the very disempowerment it seeks to combat among the San communities of Khwee and Sehunong. This article seeks to explore how notions of power and power relations influence how the San perceive themselves in the social fabric, which in turn influences their perceived participation and conceptualisation of empowerment as embedded in the discourse of community participation. The data is from a qualitative multiple-case study using semi- structured interviews and focus groups. The findings suggested that since the San are considered to be socially inferior, they are not only left out of decision making and need to be integrated but most importantly, they are disadvantaged by the various institutional and relational structures which only serve the facilitation of selective empowerment.
Published in: Journal of Public Administration and Development Alternatives, Vol. 1, No.1, July 2016, p. 45-58
Keywords: Community participation - Botswana; Non-Governmental Organisations